2016
DOI: 10.1159/000448581
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the HiFocus Mid-Scala and HiFocus 1J Electrode Array: Angular Insertion Depths and Speech Perception Outcomes

Abstract: The HiFocus Mid-Scala (MS) electrode array has recently been introduced onto the market. This precurved design with a targeted mid-scalar intracochlear position pursues an atraumatic insertion and optimal distance for neural stimulation. In this study we prospectively examined the angular insertion depth achieved and speech perception outcomes resulting from the HiFocus MS electrode array for 6 months after implantation, and retrospectively compared these with the HiFocus 1J lateral wall electrode array. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 37 publications
2
39
0
Order By: Relevance
“…The decision to use the 12 months follow-up criterion is based on data of Holden et al (10) who showed that most CI recipients reach stable speech perception performance after 1 year CI experience. Ten studies that were excluded from this review (6,9,11,14,44,53,56,59,61,64) investigated speech perception within the first year. Four out of 10 studies (40%), reported a significant positive correlation between angular insertion depth and speech perception, compared with one out of seven of the included studies (14%).…”
Section: Discussionmentioning
confidence: 99%
“…The decision to use the 12 months follow-up criterion is based on data of Holden et al (10) who showed that most CI recipients reach stable speech perception performance after 1 year CI experience. Ten studies that were excluded from this review (6,9,11,14,44,53,56,59,61,64) investigated speech perception within the first year. Four out of 10 studies (40%), reported a significant positive correlation between angular insertion depth and speech perception, compared with one out of seven of the included studies (14%).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the optimal distance between electric and acoustic stimulation for the best EAS speech reception performance and long-term preservation of residual hearing is still unknown, and several aspects have to be taken into account. Different studies found varying effects of electrode insertion on speech reception for electric stimulation, with some reporting better performance with deeper insertion ( Hochmair et al 2003 ; Hamzavi & Arnoldner 2006 ; Buchman et al 2014 ; Büchner et al 2017 ) but others reporting no effect of insertion depth ( van der Jagt et al 2016 ). At the same time, deeper insertion has been shown to adversely affect hearing preservation in the implanted ear ( O'Connell et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In focussed stimulation schemes, the active electrode delivers the intended current waveform and flanking electrode contacts, which carry the opposite polarity of current to close the circuit loop, serve as the return electrodes. One example is partial tripolar (TP) stimulation, which decreases the current spread, improves spatial selectivity, and improves spectral resolution and speech performance in many CI patients (Bierer 2007;Zhu et al 2012;Srinivasan et al 2013;Padilla and Landsberger 2016). A major challenge in the clinical applicability of these stimulation modes is power consumption.…”
Section: Introductionmentioning
confidence: 99%